Antioxidative Properties of White and Red Flowered Agathi (Sesbania grandiflora) Tea and Tea Extracts - LIAOTRAKOON, Wijitra; LIAOTRAKOON, Vachiraya (Walailak Journal of Science and Technology (WJST), 2018)
The study aimed to examine the effect of agathi (Sesbania grandiflora) variety (i.e. red and white flower varieties), flower with and without pollen, and infusion times on the total phenol and tannin contents, and antioxidative activity (DPPH free radical scavenging and ferric reducing antioxidant power; FRAP) of agathi teas. The total phenol content, DPPH, and FRAP of the red flower agathi in form of dried tea were higher than those of the white variety (p < 0.05). The total phenol content of red and white flowered agathi teas were remained about 77 and 55 %, respectively (as dry basis weight) compared to the fresh flower agathi. In addition, the antioxidative activity of the agathi tea extracts significantly increased with increasing infusion time. The DPPH and FRAP of the tea extracts of flower agathi with pollen were slightly higher than those of the flower agathi without pollen tea extracts. After infusion the agathi tea with hot water (95 °C) for 10 min (time interval of 2 min), total phenol content, DPPH, FRAP, and tannin content of the red flowered agathi with pollen were the highest among all flower agathi teas (p < 0.05). Therefore, the agathi tea should be infused at 95 °C for 10 min to gain more bioactive compounds. The results indicated that the red flowered agathi tea had efficient antioxidative activity that they could be used as a potential source of natural antioxidants.